Systemic therapy for metastatic renal cell carcinoma—is timing everything? - Kotecha, Ritesh R.; Voss, Martin H. (Annals of Translational Medicine, 2019)
Timeliness of medical care for patients with newly diagnosed cancer has long been recognized as a cornerstone metric for healthcare quality. For patients with renal cell carcinoma (RCC), such considerations have largely focused on patients with localized disease awaiting curative surgery (1,2). Delays, though, often occur for patients with metastatic disease, particularly in those with symptomatic disease, and may also affect treatment outcomes.